2017
DOI: 10.12693/aphyspola.132.108
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Magnetic Field on Dark States in Transport through Triple Quantum Dots

Abstract: We theoretically study the electronic transport through a triple quantum dot system in triangular geometry weakly coupled to external metallic leads. By means of the real-time diagrammatic technique, the current and Fano factor are calculated in the lowest order of perturbation theory. The device parameters are tuned to such transport regime, in which coherent population trapping of electrons in quantum dots due to the formation of dark states occurs. The presence of such states greatly influences transport pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The fingerprint of the Berry-phase effect in spin-molecule systems is determined by the suppression of tunnel splitting when different spin tunneling paths interfere destructively for certain values of the transverse magnetic field. [9][10][11] More recently, electron transport across a three-terminal SMM has been explored in various studies, and the Coulomb blockade has been demonstrated. The Kondo effect oscillations as a function of the transverse magnetic field have also been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fingerprint of the Berry-phase effect in spin-molecule systems is determined by the suppression of tunnel splitting when different spin tunneling paths interfere destructively for certain values of the transverse magnetic field. [9][10][11] More recently, electron transport across a three-terminal SMM has been explored in various studies, and the Coulomb blockade has been demonstrated. The Kondo effect oscillations as a function of the transverse magnetic field have also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The fingerprint of the Berry‐phase effect in spin‐molecule systems is determined by the suppression of tunnel splitting when different spin tunneling paths interfere destructively for certain values of the transverse magnetic field. [ 9–11 ]…”
Section: Introductionmentioning
confidence: 99%